Blood clot formation in blood bags: Operational evidence, contributing factors, and mitigation strategies in a public blood transfusion service (Research, Society and Development, 2026)
The formation of clots in blood bags represents a critical event for transfusion quality and safety, being associated with operational failures throughout the hemotherapy cycle. Identifying these events requires a systemic approach, considering the interaction between technical, human, and organizational factors involved in the processes of collection, homogenization, and monitoring of blood components. This study aims to analyze clot formation in blood bags within a public blood transfusion service, based on operational and regulatory evidence, identifying contributing factors throughout the blood transfusion cycle and discussing mitigation strategies aimed at strengthening process quality and transfusion safety. This is an observational, retrospective, and documentary study with a quantitative and operational approach, developed from routine records of a public blood transfusion service located in Northeast Brazil, covering the period from January to December 2025. The results demonstrated that clot formation occurred predominantly without exceeding the classic acceptable time and volume limits, indicating that the overall collection time, in isolation, was not a primary determining factor. Clot formation in blood bags should be understood as a systemic event affecting transfusion quality and safety. Preventing these events requires strengthening the standardization of phlebotomy, continuous monitoring of processes, training of teams, and the structured application of root cause analysis, contributing to the reduction of losses, improvement in the quality of blood components, and increased safety of care in public hemotherapy services.